Effect of time to simulation and treatment for patients with oropharyngeal cancer receiving definitive radiotherapy in the era of risk stratification using smoking and human papillomavirus status. Issue 4 (22nd January 2018) - Amsbaugh, Mark J.; Yusuf, Mehran; Cash, Elizabeth; Silverman, Craig; Potts, Kevin; Dunlap, Neal
Abstract: Background: The effect of increasing time to definitive radiotherapy (RT) for patients with oropharyngeal squamous cell carcinoma (SCC) is unknown. Methods: Nodal tumor volumes at staging and simulation were compared for patients with oropharyngeal SCC. Time from staging to initiation of RT was tabulated. The primary endpoint of interest was nodal progression at simulation. Results: Increasing time to simulation was associated with nodal progression in 144 patients (r = 0.474; P < .001). Patients with human papillomavirus (HPV)‐associated oropharyngeal SCC were more likely to have nodal progression (50% vs 26%; P = .008). A threshold of 32 days was associated (sensitivity 77.9% and specificity 60.2%) with nodal progression ( P < .001). Increasing time from staging to treatment initiation was associated with a greater risk of distant failure (hazard ratio [HR] 4.157; 95% confidence interval [CI] 1.170‐14.764) but not progression‐free survival (PFS; P = .179) or overall survival (OS; P = .474). Conclusion: Increasing time before RT for patients with oropharyngeal SCC is associated with nodal progression and increased hazard of distant failure, although not PFS or OS in our population.